Colletotrichum on coffee trees in south of minas gerais -Brazil: physiological, molecular and pathogenic description - Armesto, Cecilia; Gonçalves Martins Maia, Fernanda; Monteiro, Fernando Pereira; de Abreu, Mario Sobral (Coffee Science - ISSN 1984-3909, 2017)
Fungi of the genus Colletotrichum spp. are cosmopolitan and are responsible for disease in many plants of agronomic importance. In coffee crops, three species have been described: Colletotrichum acutatum, Colletotrichum kahawae and Colletotrichum gloeosporioides. In Brazil were only reported the species C. acutatum and C. gloeosporioides, which symptoms are attributed as antracnoses, dieback and blister spot. This study evaluates the population of Colletotrichum spp. through morpho-physiological, genetic and pathogenic characteristics, in several coffee plantations in the southern of Minas Gerais. All isolates showed similar morphological and physiological characteristics, being identified as C. gloeosporioides. The best medium for mycelial growth was agar-malt extract with pH 5.5 and for spore production oat-agar medium with pH 6.5. When inoculated on berries, all isolates were pathogenic with variable levels of aggressiveness, but only 57% of these were pathogenic for hypocotyls. Three isolates, I-9, I-24 and I-26, were identified featuring the highest rates of aggressiveness in berries and hypocotyls.